High-grade serous cancer of left fallopian tube with right inguinal lymph node enlargement: a case report - Zhou, Aizhi; Gu, Weiyong; Yang, Yumei; Chen, Xin; Ye, Wenfeng; Wang, Mei (Frontiers in Oncology, 2025)
A 47-year-old woman with a two-month history of right inguinal lymphadenopathy visited Shanghai Pudong New Area People’s Hospital for a biopsy. Histopathological and immunohistochemical analyses revealed a metastasis of high-grade serous carcinoma, likely of gynecological origin. A PET-CT scan identified a tumor in the left adnexa, with no other organ involvement. The patient underwent primary cytoreduction, including laparoscopy, hysterosalpingo-oophorectomy, omentectomy, and resection of the right deep inguinal lymph nodes at the Hospital of Obstetrics and Gynecology. No residual disease was found post-surgery. Pathological examination revealed high-grade serous cancer in the fimbria of the left fallopian tube and left ovary, while the right deep inguinal lymph nodes were negative. The patient received standard chemotherapy (Carboplatin and Taxol) and showed no new lesions after three cycles, as confirmed by imaging.